Unveiling a de novo variant: Clinical progression and management challenges in a case of developmental and epileptic encephalopathy – A case report - Norma E de León Ojeda; Fridha V Villalpando-Vargas; Fabrizio A Mortola; Juan C Barrera de Leon; Tania P Sánchez-Murguía; Jonathan A Cisneros-Orozco; Alioth Guerrero-Aranda (SAGE Open Medical Case Reports)
Developmental and epileptic encephalopathies (DEEs), such as SYNGAP1 -related DEE, are marked by severe developmental delays and pharmaco-resistant seizures due to specific genetic variants. This case report focuses on a 9-year-old male with a de novo SYNGAP1 variant (c.1267del, p.Tyr423Metfs*17), illustrating the diagnostic and treatment challenges. Initially experiencing developmental delays and later, misdiagnosed tics, he was diagnosed with epilepsy with eyelid myoclonia at seven. His case includes key SYNGAP1 encephalopathy symptoms: intellectual disability, behavioral issues, and generalized epilepsy resistant to antiseizure medication. The identification of a specific variant adds to our knowledge, suggesting the necessity of considering SYNGAP1 -related DEE for unexplained neurodevelopmental delays and seizures. This case underlines the need for a personalized treatment approach focusing on quality of life and symptom management, advancing our understanding and treatment practices for genetic developmental and epileptic encephalopathy.